International health care management - Savage, Grant T. 1954- (Emerald, 2005)
This fifth volume of Advances in Health Care Management examines international health care management. It consists of 12 papers, one of which serves as an introduction, with the other papers arranged into three sections. The first section on patients and providers focuses on such issues as how socio-cultural forces affect the health care experience; how hospital providers function differently under various governance structures; how global strategies affect providers and patients; and why and how provider organizations should consider integrating within a health delivery system. The second section on policy and management addresses such dilemmas as whether some health care issues are impossible to solve through traditional policy reforms; how international refugees should receive health care; and whether policy reform lessons from other countries can be adapted and applied to transform another country's health system.-The third and final section on performance and management addresses issues such as whether the quality of care can be managed at the hospital level, how human resource management can be benchmarked within and across health care organizations, how health care informatics and telemedicine can improve the continuity of care, and whether different ways of accessing care within health systems can be systemically compared and improved. Authors from Australia, Chile, Finland, France, Germany, Greece, South Africa, Taiwan, the United Kingdom, and the United States of America contributed to this volume. They explore the delivery and organization of care in health systems from Africa, Asia, Australia, Europe, North America, and South America, encompassing more than 20 countries in their comparisons. The papers included in this volume were only accepted following a rigorous peer review process.-Each paper, whether solicited or responding to our open call, went through a double-blind review and revision process. The result is a select collection of outstanding papers.
Keywords: Health services administration.; elektronické knihy; electronic books